2008
DOI: 10.1149/1.2956969
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Methods to Enhance the Capacitance in Activated Carbon/Polyaniline Composites

Abstract: Activated carbon/polyaniline composites have been prepared using different electrochemical methods: single-step potentiostatic polymerization, multiple-step potentiostatic polymerization, and potentiodynamic polymerization with the anodic potential limits being fixed at either 0.75 or 1 V ͑vs Ag/AgCl͒. The prepared composite samples were characterized by cyclic voltammetry, galvanostatic charge-discharge tests, electrochemical impedance spectroscopy, and Fourier transform infrared ͑FTIR͒ spectroscopy. The synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 42 publications
(52 reference statements)
3
23
0
Order By: Relevance
“…Assuming a contribution of 10 F g À1 from the NP-CNF substrate, the specific capacitance of PANI can be estimated as 570 F g À1 PANI . This value is comparable to several earlier studies [7,19]. However, the SEM image ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Assuming a contribution of 10 F g À1 from the NP-CNF substrate, the specific capacitance of PANI can be estimated as 570 F g À1 PANI . This value is comparable to several earlier studies [7,19]. However, the SEM image ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Overall, these authors concluded that the potentiodynamic technique produces a more uniform PANI film due to periodic interruptions during polymerization between consecutive sweeps. This conclusion was also confirmed by Bleda-Matinez and co-workers [19] when electrodepositing PANI on high surface areaeactivated carbon. However, they preferred the potentiostatic method as it allowed the formation of a more porous PANI film that resulted in higher capacitance.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The incorporation of active materials such as transition metal oxides [8][9][10] and conducting polymers [11][12][13][14][15] will increase the volumetric charge and discharge capacities of porous carbon. In this work, a composite electrode consisting of bimodal porous carbon and polypyrrole (PPy) was prepared by the electropolymerization of pyrrole within the macropores of bimodal porous carbon.…”
Section: Introductionmentioning
confidence: 99%
“…An example for this possibility are carbon/conducting polymer composites, which can take the advantage from both, the double layer mechanism provided by porous carbon materials and the pseudo-capacitance contribution from conducting polymers. Our research group has prepared polyaniline (PANI)/ porous carbon composites by both chemical 16) and electrochemical polymerization methods 17) and those composites were characterized in terms of porosity and performance as electrochemical capacitors.…”
Section: Polyaniline/porous Carbon Electrodes By Chemical and Electromentioning
confidence: 99%